Etiquette in Islam - almatalka, Tagreed Hassan (Journal of Islamic Sciences, 2019)
Praise be to Allah, this research which is tagged "Etiquette in Islam," has been completed. This research spoke about the etiquette, its concept, types, and the difference between the etiquette and the protocol. Herein, I declared that etiquette is the main behavior's motive.In addition, I talked about types of internal and external etiquette, and everything related to, besides showing that persons begin acting the etiquette firstly with themselves, and then with relative, or non relative people, Muslims, or non-Muslims. Descriptive analytical and deductive approaches were followed in this research, as they fit with the study's nature.Finally, I mentioned a set of the most important conclusions, that the etiquette is essential in the Muslim's life, and the main source of the etiquette is the Islamic legislation, with its sources. I also stated some recommendations for Muslims, parents, and educators in particular. First of all is the religiosity of Allah in treating themselves, their children, and the others. As contacting in a respectful manner, which reflects the true image of Islam and Muslims, and proves to all that Islam is the origin of ethics and virtuous ethics.
Keywords: Etiquette; Protocol; Islam